ALTERAÇÕES DO SONO EM PROFESSORES UNIVERSITÁRIOS: uma revisão integrativa - Moneta Moraes, Bruno Fernando (2022)
Introduction: University professors, from different areas of knowledge, constantly add, in addition to their workload in front of the student, extra-class tasks that lengthen their working hours, multiple jobs and execution of tasks in reduced terms. Therefore, these professionals may present negative conditions in relation to their sleep, including sleep deprivation and reduction in the sleep quality, affecting their well-being and quality of life. Objective: to highlight the main sleep disorders in university professors, pointing out the associated factors and the repercussions of these occurrences. Materials and methods: integrative review carried out on the PubMed, Web of Science, Scopus, CINAHL and Virtual Health Library portals, with original studies published between 2002 and 2021, in Portuguese, English and Spanish. Results and Conclusions: after applying the selection criteria, five studies were chosen, published between 2018 and 2021, which showed sleep disorders, as well as their relationship with other aspects of health. Sleep disorders in university professors were characterized by a reduction in the subjective quality of sleep and daytime sleepiness. Aspects related to the work of the university professor influenced the quality of sleep, such as long hours, excessive work, workaholism and high demand at work. The reduction in sleep quality and daytime sleepiness had an impact on perceptions of quality of life and aspects related to Burnout. It is essential to search for robust scientific data, broadly exploring sleep disorders in university professors and monitoring their repercussions.